2013
DOI: 10.1007/s10661-013-3104-8
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of heavy metals in Spinacia oleracea irrigated with paper mill effluent and sewage

Abstract: The present study on heavy metal contamination in soil and their accumulation in edible part (leaves) and roots of Spinacia oleracea (Spinach) on irrigation with paper mill effluent (PME)/sewage revealed that there was significant increase in the nickel (Ni, +227.17 %) content of the soil irrigated with PME, whereas in the soil irrigated with sewage chromium (Cr, +274.84 %), iron (Fe, +149.56 %), and cadmium (Cd, +133.39 %), contents were increased appreciably. The value of enrichment factor (EF) for Ni (3.27)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 17 publications
2
8
2
Order By: Relevance
“…Enrichment of various metals was also paddy crops after paper mill effluent irrigation. The findings are very much in accordance with Pathak et al [9,10].…”
Section: Effect On Biochemical Constituents and Metals In T Foenum-gsupporting
confidence: 92%
See 1 more Smart Citation
“…Enrichment of various metals was also paddy crops after paper mill effluent irrigation. The findings are very much in accordance with Pathak et al [9,10].…”
Section: Effect On Biochemical Constituents and Metals In T Foenum-gsupporting
confidence: 92%
“…Heavy metals are very harmful because of their non-biodegradable nature, long biological half-lives and their potential to accumulate in different body parts [6][7][8]. Most of the heavy metals are extremely toxic because of their solubility in water [3,9,10]. Wastewater contains substantial amounts of toxic heavy metals, which create problems [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The present data revealed that the level of heavy metals in soil increased as per dilution quantity of PME. In the present study heavy metal content such as Pb (17.40±0.78 mg/ kg), Cr (32.02±1.18 mg/kg), Ni (67.02±1.46 mg/kg) and Cd (6.35±0.49 mg/kg) with 100% PME irrigated soil was higher than those reported by Pathak et al (2013) for Cr (29.53±3.33 mg/kg) and Cd (6.11±1.74 mg/kg) in 100% PME irrigated soil, except Ni (206.18±13.44 mg/kg) in PME irrigated soil at Haridwar, whereas Sinha et al (2008) found Fe (14,285 ± 1244 mg/kg), Cr (197.76 ± 12.83 mg/kg) and Zn (104.91 ± 0.97 mg/kg) in soils treated with different tannery sludge applications. PME irrigation increased Pb, Cr, Cd and Ni of the soil.…”
Section: Resultscontrasting
confidence: 74%
“…Ef value for Pb and Ni showed deficiency to mineral enrichment with 10%, 25%, 50%, 75% and 100% PME irrigation. The Ef value of Ni for soil was lower than Ni (3.27) as reported by Pathak et al (2013) for PME irrigated soil. also reported more Ef for Cr (11.24), Cd (5.04) in soil irrigated with Sugar mill effluent.…”
Section: Resultscontrasting
confidence: 61%
“…Heavy metals are very harmful because of their non-biodegrable nature, long biological half-lives and their potential to accumulate in different body parts [6][7][8]. Most of the heavy metals are extremely toxic because of their solubility in water [3,9,10]. The major short comings of the conventional treatments are low efficiency at low concentration of heavy metals, expensive handling and safe disposal of toxic sludge [11].…”
Section: Introductionmentioning
confidence: 99%